Quantifying Heat Transfer Characteristics of the Kroll Reactor in Titanium Sponge Production - Wang, Wenhao; Wu, Fuzhong (Frontiers in Energy Research, 2021)
Various reactors with different sizes have been widely used for the production of titanium sponge in the Kroll process. But the further commercialization of the forced heat transfer design of the Kroll reactor is limited by lack of standard parameter to evaluate its convective heat transfer characteristics. This work proposes to evaluate and compare the Kroll reactor with the dimensionless Nusselt number. The results shown that the heat transfer coefficients for both surfaces increase with the volume flow rate of cooling air for each dimensionless temperature, and the heat transfer coefficients of the external surface of the reactor are higher than that of the internal surface of the heater. And new correlations regarding the Nusselt number between the cooling air and the external surface of the reactor or the internal surface of the heater are obtained based on experimental data, while the characteristics of the cooling air, equipment and operation parameters are considered.